Better Dispersability of Un-Functionalized Multiwalled Carbon Nanotubes Through Sonication Techniques - Lal, Madan; Verma, Gaurav; Dharamvir, Keya (Asian Journal of Chemistry, 2012)
Different sonication techniques have been applied to increase dispersion efficiency of carbon nanotubes. During sonication (probe and bath), the effects of good dispersion on un-functionalized multiwalled carbon nanotubes (MWCNTs) and microstructure structure were characterized by tunneling electron microscopy (TEM) and Raman spectroscopy. The particle size distribution of the dispersed multiwalled carbon nanotubes was determined by using dynamic light scattering (DLS). The estimated length and diameter was observed to be ca. 210 and 9.44 nm (bath sonication) and ca. 396 and 10.04 nm (probe sonication) from the TEM images.